"'Cause You Can't Play This by Yourself": Athletes' Perceptions of Team Influence on Their Precompetitive Psychological States. Issue 2 (3rd April 2018) - Wolf, Svenja A.; Harenberg, Sebastian; Tamminen, Katherine; Schmitz, Hanna
Abstract : Although correlational studies indicate that team attributes are related to athletes' precompetitive psychological states, it is unknown how team members experience these relationships. The present study's purpose was to investigate athletes' perceptions of precompetitive team influence. Consequently, we worked from a constructivist realist position and used qualitative methods (interviews with competitive team-sport athletes). An inductive content analysis revealed that athletes perceived established and novel team characteristics and processes to influence their precompetitive psychological states. Athletes perceived these influences as both adaptive and maladaptive, and it appeared that they were qualified by contextual factors as well as intuitive regulatory attempts.